2009
DOI: 10.1111/j.1471-0307.2008.00441.x
|View full text |Cite
|
Sign up to set email alerts
|

Moisture sorption characteristics of curd (Indian yogurt) powder

Abstract: The moisture sorption behaviour of curd (Indian yogurt) powder was studied at 20, 30, 40 and 50°C for water activity ranging from 0.07 to 0.85. GAB, BET, Henderson, Halsey, Chung & Pfost, Smith, Oswin and Peleg models were applied to analyse the data. Estimated parameters and fitting ability for sorption models were evaluated. The GAB model showed the best fit to the sorption data of curd powder at 20, 30 and 40°C, and the Peleg model fitted well at 50°C.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 23 publications
2
2
0
Order By: Relevance
“…Palipane and Driscoll (1992) explained this phenomenon as the breaking away of water molecules from the sorption sites when activated at higher energy levels and decreases the EMC. Similar findings have been reported in literature of sorption isotherm study of yoghurt powders (Koc et al 2010a;Varghese et al 2009). A sharp increase in EMC was observed at higher a w (a w [0.50) for all the temperatures studied and could be explained by the dissolution of sugar in the sorbed water vapour (Kaymak-Ertekin and Gedik 2004; Maroulis et al 1988).…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…Palipane and Driscoll (1992) explained this phenomenon as the breaking away of water molecules from the sorption sites when activated at higher energy levels and decreases the EMC. Similar findings have been reported in literature of sorption isotherm study of yoghurt powders (Koc et al 2010a;Varghese et al 2009). A sharp increase in EMC was observed at higher a w (a w [0.50) for all the temperatures studied and could be explained by the dissolution of sugar in the sorbed water vapour (Kaymak-Ertekin and Gedik 2004; Maroulis et al 1988).…”
Section: Resultssupporting
confidence: 89%
“…The plots of equilibrium moisture content of SYP and the corresponding water activity at selected storage temperatures were used to generate sorption isotherms. In the present study, eight sorption models were used which have been proposed for sugar-rich dehydrated food powders in the literature (Iglesias and Chirife 1982;Koc et al 2010a;Mundada and Hathan 2012;Sormoli and Langrish 2015;Varghese et al 2009). A non-linear least-square regression analysis was done to evaluate the models.…”
Section: Modelling Of Sorption Isothermsmentioning
confidence: 99%
“…On the basis of the highest R 2 , lowest E%, SSE, RMSE and better random residual plots, the Oswin model found best fitted model followed by GAB, Smith and Peleg model. The present results were followed with the other researchers’ work reported by Langova and Stencl (2014) for whole milk powder, Varghese et al (2008) for yogurt powder and Yu et al (2013) for bovine colostrum powder.…”
Section: Resultssupporting
confidence: 83%
“…Sorption isotherms of several western dairy products including milk powder, whey protein, lactose, casein, whey powder, yoghurt, and cheese have been reported, but the published report on Indian dairy products is limited. Information on moisture sorption isotherm of Kalakand (Deshmukh et al 2018), Shrikhand (Khojare, 2018), Bottle Guard Burfi (Quadri et al 2016), Cham-Cham ( Puri and Khamuri, 2015), Sandesh (Khojare, 2014;Khojare and Hembade, 2015;Sahu and Das, 2010), Dietetic Rabri (Ghayal et al 2013), Dietetic Chhana Kheer (Gautam et al 2018), Peda (Biradar et al 1985;Kumar et al 2012), ready to use Basundi mix (Sharma et al 2009), Curd powder (Varghese et al 2008), Chhana podo (Rao et al 2006. ), Milk Burfi (Ramakrishna et al 2005, Kheer (Jayendra Kumar et al 2005), Dudh churpi (Hossain et al 2002), Khoa (Sawhney and Cheryan, 1988) and Chhana powder and Casein (Bandyopadhyay et al 1987) have been reported.…”
Section: Introductionmentioning
confidence: 99%